The adaptation advantage : let go, learn fast, and thrive in the future of work - McGowan, Heather (Consultant); Shipley, Chris (John Wiley & Sons, 2020)
"Three profound and fast-moving changes are disrupting work and society, and in the process stripping us of our comfortable work-centric identities. First, our mental models of employment and education are still based on institutions developed in the early twentieth century, as work first moved from farm to factory and then to factory to office. But they no longer work in an economy that is constantly changing. As a result, our current work identities are, in many cases, stifling our ability to adapt to new and technology-driven opportunities. Second, long-held cultural norms have collapsed. Family and sexuality norms are changing, and American demographics are changing. Third, Digitization is deconstructing the old economy. As a result of these forces, stress at work is at an all-time high. Gallup reports 70% of workers are disengaged. As people read predictions about the future of work, they become fearful that they will become irrelevant and unemployable in the new world. This book offers a refreshing, empowering take on the need for, and power of, humans in the future of work. It explains the necessity of creating a culture of continuous learning, and rethinking talent management, to create a passionate, engaged workforce. The new job of leaders is helping people adapt to change and this book explains how. The solution is to create new systems that detach identity from work and connect it to purpose--This purpose, then, becomes the motivation, and self-generating fuel for learning, work, deeper engagement, and new forms of empowering identity"--